Iceland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper reports on the technical aspects of the model-based inflation forecasts of the Central Bank of Iceland (CBI) and the monetary transmission mechanism in Iceland. The paper summarizes the structure and results of time series models employed by the CBI to forecast inflation and quantify lags in the transmission of monetary policy changes. The paper also briefly discusses recent inflation trends, including the IMF staff's estimate of the exchange rate pass-through. The paper presents some remarks on potential distortions in the financial market pass-through of monetary policy changes.